N‐terminal pro‐B‐type natriuretic peptide and high‐sensitivity troponin T hold diagnostic value in cardiac amyloidosis. (11th January 2023) - Vergaro, Giuseppe; Castiglione, Vincenzo; Aimo, Alberto; Prontera, Concetta; Masotti, Silvia; Musetti, Veronica; Nicol, Martin; Cohen Solal, Alain; Logeart, Damien; Georgiopoulos, Georgios; Chubuchny, Vladyslav; Giannoni, Alberto; et al.
Abstract : Aims: Cardiac amyloidosis (CA) is associated with an elevation of natriuretic peptides and troponins, predicting outcome. Nevertheless, the diagnostic yield of these biomarkers has not been extensively investigated. This study aimed to evaluate the diagnostic performance for CA of N‐terminal pro‐B‐type natriuretic peptide (NT‐proBNP) and high‐sensitivity troponin T (hs‐TnT). Methods and results: Patients with suspected CA ( n = 1149) underwent a diagnostic work‐up in three centres in Italy, France ( n = 343, derivation cohort), and United Kingdom ( n = 806, validation cohort). Biomarker values with either 100% sensitivity or ≥95% specificity were selected as rule‐out/rule‐in cut‐offs, respectively. In the derivation cohort, 227 patients (66%) had CA, and presented with higher NT‐proBNP and hs‐TnT. NT‐proBNP 180 ng/L and hs‐TnT 14 ng/L were selected as rule‐out cut‐offs, and hs‐TnT 86 ng/L as rule‐in cut‐off. NT‐proBNP <180 ng/L or hs‐TnT <14 ng/L were found in 7% of patients, and ruled out CA without false negatives. In the validation cohort, 20% of patients (2% false negatives) had NT‐proBNP <180 ng/L or hs‐TnT <14 ng/L, and 10% showed both biomarkers below cut‐offs (0.5% false negatives). These cut‐offs refined CA prediction when added to echocardiographic scores in patients with a haematologic disease or an increased wall thickness. In the validation cohort, the 86 ng/L hs‐TnT cut‐off ruled in 20% of patients (2% false positives). NT‐proBNP and hs‐TnT cut‐offs retained their rule‐out and rule‐in performance also in cohorts with CA prevalence of 20%, 10%, 5% and 1% derived from the original cohort through bootstrap analysis. Conclusions: Cardiac biomarkers can refine the diagnostic algorithm in patients with suspected CA. NT‐proBNP <180 ng/L and hs‐TnT <14 ng/L reliably exclude the diagnosis, both in the overall population and subgroups referred for either AL‐CA or cardiac (pseudo)hypertrophy. Abstract : Cardiac biomarkers hold diagnostic value in cardiac amyloidosis (CA). The diagnosis can be reliably excluded when N‐terminal pro‐B‐type natriuretic peptide (NT‐proBNP) is <180 ng/L and high‐sensitivity troponin T (hs‐TnT) is <14 ng/L.